Navigating the current landscape of ocean observations: an overview from platform infrastructures to networks related to ocean time series - von Jackowski, Anabel (Frontiers in Marine Science, 2025)
Increasing global temperatures, biodiversity loss, and pollution are among the major transformative changes affecting terrestrial and marine ecosystems. The marine biome can be observed and monitored using ocean observations with satellite-based platforms, tagging of animals, autonomous platforms and vehicles, and ship-based measurements. Sustaining ocean observations at a given location over time are known as ocean time series. For example, stationary platforms like moorings record data autonomously at one location over time, while ship-based time series stations are sampled using discrete measurements at varying sampling frequencies throughout a given year. Ocean observations feed into networks that either focus on obtaining data, e.g., similar instruments, or a social focus that aims to connect participants, e.g., early career or science-policy interface. These platforms and associated networks feed into the Framework for Ocean Observing (FOO) with a set of Essential Ocean Variables (EOVs) and the Ocean Best Practices System (OBPS) developed by the global ocean observing community. The range of ocean observing activities around the world creates a complex landscape, which can be particularly difficult to navigate for early career ocean professionals (ECOPs). ECOPs face higher barriers to entering the United Nations Decade of Ocean Science for Sustainable Development ("UN Ocean Decade") than others despite actively contributing to ocean observations and playing the most significant role in the success of sustainability transformations. The review aims to provide an overview of the organizations and networks associated with ocean observations, motivate ECOPs to actively get involved in the ongoing UN Ocean Decade (2021-2030), and join or create new initiatives within the existing landscape. Ocean observations harbor an extraordinary benefit for a large diversity of end-users far beyond the scientific community, and there is a need to engage the next generation of ocean leaders as we transition to live and manage this blue planet sustainably.